Race factors affecting performance times in elite long-track speed skating - Noordhof, D. A.; Mulder, R. C. M.; de Koning, J. J.; Hopkins, W. G. (International Journal of Sports Physiology and Performance, 2016)
Analysis of sport performance can provide effects of environmental and other venue-specific factors in addition to estimates of within-athlete variability between competitions, which determines smallest worthwhile effects.